Differences in MDS‐UPDRS Scores Based on Hoehn and Yahr Stage and Disease Duration. Issue 4 (11th March 2017) - Skorvanek, Matej; Martinez‐Martin, Pablo; Kovacs, Norbert; Rodriguez‐Violante, Mayela; Corvol, Jean‐Christophe; Taba, Pille; Seppi, Klaus; Levin, Oleg; Schrag, Anette; Foltynie, Thomas; Alvarez‐Sanchez, Mario; Arakaki, Tomoko; et al.
Abstract: Background: The Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS‐UPDRS) is a newly developed tool to assess Parkinson's disease (PD). Changes in scores on the scale over the course of PD, including increasing disease duration and Hoehn and Yahr (HY) stages, have not been described. The objectives of this study were to analyze MDS‐UPDRS scores on Parts I through IV and their differences based on HY stage and disease duration in a large cohort of patients with PD. Methods: For this cross‐sectional study, demographic data and MDS‐UPDRS scores were collected, including HY stage. Subscores on MDS‐UPDRS Parts I through IV were analyzed using 1‐way analyses of variance for each HY stage and in 5‐year increments of disease duration. Part III (motor assessment) scores were analyzed separately for on and off states. Results: The mean age of the 3206 patients was 65.8 ± 10.6 years, 53.3% were men, the mean disease duration was 11.5 ± 4.6 years, and the median HY stage was 2 (range, 0–5); 2156 patients were examined in an on state and 987 were examined in an off state. Scores for all MDS‐UPDRS parts increased significantly through HY stages 1 through 5, with an average increase of 3.8, 7.7, 14.6, and 2.0 points consecutively for parts I through IV, respectively. For the 5‐year increments of disease duration, MDS‐UPDRS subscores increased by an average of 1.6, 3.3, 4.2, and 1.4 points consecutively for parts I through IV, respectively. This increase was significant only during the first 15 years of disease for all 4 parts, including part III scores evaluated in both on and off states. Conclusions: MDS‐UPDRS scores for all 4 parts increase significantly with every HY stage and also with 5‐year increments of disease duration in the first 15 years of the disease.